Cys–Cys and Cys–Lys Stapling of Unprotected Peptides Enabled by Hypervalent Iodine Reagents. (8th March 2021) - Ceballos, Javier; Grinhagena, Elija; Sangouard, Gontran; Heinis, Christian; Waser, Jerome
Abstract: Easy access to a wide range of structurally diverse stapled peptides is crucial for the development of inhibitors of protein‐protein interactions. Herein, we report bis‐functional hypervalent iodine reagents for two‐component cysteine‐cysteine and cysteine‐lysine stapling yielding structurally diverse thioalkyne linkers. This stapling method works with unprotected natural amino acid residues and does not require pre‐functionalization or metal catalysis. The products are stable to purification and isolation. Post‐stapling modification can be accessed via amidation of an activated ester, or via cycloaddition onto the formed thioalkyne group. Increased helicity and binding affinity to MDM2 was obtained for a i, i+ 7 stapled peptide. Abstract : Bifunctional hypervalent iodine reagents for two‐component cysteine‐cysteine and cysteine‐lysine stapling are reported. Efficient and selective stapling on non‐protected peptides was observed, and post‐stapling modification could be easily achieved using reactive esters or cycloaddition on the thioalkynes formed on the cysteine residue. One stapled peptide displayed both enhanced helicity and binding to the MDM2 protein.